A performance evaluation model of a high concentration photovoltaic module with a fractional open circuit voltage-based maximum power point tracking algorithm. (April 2016) - Huang, Yu-Pei; Hsu, Sheng-Yu
Highlights: A performance evaluation model of a high concentration photovoltaic module is proposed. The output power performance is simulated and assessed by MATLAB/Simulink software. The magnitude of the optical loss caused by Fresnel lens shape deformation and AM is modeled and quantized. Two maximum power tracking techniques are simulated and compared. The simulation results suggest that the fractional open circuit voltage technique has better performance. Abstract: High concentration photovoltaic (HCPV) modules employing high-efficiency III–V solar cells promise greater system-level efficiency than conventional photovoltaic (PV) systems. Nevertheless, the output power of an HCPV system is very sensitive to rapidly fluctuating tracking errors and weather patterns. The fractional open circuit voltage (FOCV) based maximum power point (MPP) tracking technique benefits from simplified processing circuits with speed response. To investigate the feasibility of using the FOCV technique for MPP estimation on HCPV modules, a theoretical model and simulation are presented in this study. A MATLAB-based MJSC circuit model of an HCPV module with buck-type converter and load is proposed and validated. In addition, the magnitude of the optical loss caused by Fresnel lens shape deformation and air mass (AM) ratio is modeled and quantized. The FOCV technique is then employed and compared with the conventional perturb and observe (P&O) method on the HCPV module under varying irradiance and temperature conditions to study its effectiveness. The results suggest that the FOCV technique could help an HCPV module to attain greater power efficiency.